Inclisiran: a new generation of lipid-lowering siRNA therapeutic - Zhang, Yanzhen; Chen, Huaigang; Hong, Lang; Wang, Hong; Li, Bin; Zhang, Mengyin; Li, Jiamei; Yang, Liu; Liu, Fan (Frontiers in Pharmacology, 2023)
Atherosclerotic heart disease (AHD) is a major cause of morbidity and mortality worldwide. Lowering low-density lipoprotein cholesterol (LDL-C) levels is a key strategy to prevent and treat AHD. Inclisiran is a novel siRNA drug that targets proprotein convertase subtilisin/kexin type 9 (PCSK9) gene expression and reduces LDL-C levels with only two or three injections per year. This review summarizes the mechanism, efficacy, safety, and applications of Inclisiran in various populations and settings, based on recent literature. It also compares Inclisiran with other lipid-lowering drugs, especially other PCSK9 inhibitors. We conclude that Inclisiran is a promising lipid-lowering agent that can provide convenience and effectiveness for patients with high cardiovascular risk. However, some challenges and limitations remain for Inclisiran, such as its long-term safety and efficacy, its cost-effectiveness and accessibility, and its interactions and synergies with other drugs. These issues need further investigation and evaluation in future studies.